2020
DOI: 10.3892/ol.2020.11810
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase inhibition decreases esophageal squamous carcinoma cell migration and invasion

Abstract: Telomerase has been shown to be associated with a variety of cancer types. To elucidate the role of telomerase in esophageal squamous carcinoma (ESCC), tissue samples from 100 patients with ESCC, and paired paracancerous tissues from 75 of these patients, were collected for use in the present study. Using immunohistochemical analysis, the expression of telomerase reverse transcriptase (hTERT) in the cytoplasm of ESCC cells was revealed to be significantly higher compared with that in paracancerous tissues, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Besides the antimalaria activity, DHA has been reported to exhibit significant anticancer activity in a variety of tumors (Dai et al, 2021), including lung cancer (Jiang et al, 2016), ovarian cancer (Li et al, 2018), MM (Wu et al, 2020), and hepatocellular carcinoma (Zou et al, 2019). Previous study demonstrated that inhibition of telomerase activity could reduce the proliferation and migration of esophageal cancer cells (Li et al, 2020). Our data showed that DHA could evidently downregulate the expression of hTERT both on mRNA and protein level.…”
Section: Discussionsupporting
confidence: 53%
“…Besides the antimalaria activity, DHA has been reported to exhibit significant anticancer activity in a variety of tumors (Dai et al, 2021), including lung cancer (Jiang et al, 2016), ovarian cancer (Li et al, 2018), MM (Wu et al, 2020), and hepatocellular carcinoma (Zou et al, 2019). Previous study demonstrated that inhibition of telomerase activity could reduce the proliferation and migration of esophageal cancer cells (Li et al, 2020). Our data showed that DHA could evidently downregulate the expression of hTERT both on mRNA and protein level.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, increased migration and transmigration activity of U2OS cells was observed [62]. On the other hand, the silencing of hTERT via siRNA in esophageal squamous carcinoma cells decreased cell migration and invasiveness, but did not affect cell proliferation [63].…”
Section: Discussionmentioning
confidence: 93%
“…Western blot for liver-specific proteins was performed as described previously. 16 Tumor cells were harvested and lysed with RIPA buffer (KeyGEN BioTECH, Nanjing, Jiangsu, China), and protein concentration was quantified with a bicinchoninic acid protein assay kit (KeyGEN BioTECH, Nanjing, Jiangsu, China). The proteins were boiled with 5X loading buffer, and 40-µg aliquots of total protein were separated using 12.5% SDS-PAGE gels, prior to transfer onto PVDF membranes (EMD Millipore, Darmstadt, Hessen, Germany).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The expression of CK7, CK20 (Cytokeratin 7, Cytokeratin 20, both are cytoskeleton protein, used as biomarker of ICC), HEP1, GPC3, Arg1 (Hepatocyte paraffin 1, Glypican 3, Arginase-1, all are biomarker of HCC), and Ki67 (proliferation cell-associated nuclear antigen in tumor tissues) was assessed as reported before. 16 Cells were centrifuged at 1000 rpm for 5 min, and the pellet was embedded in paraffin for further immunohistochemical detection. The slices of tissue or cell were placed in an oven at 65°C for 1 h, then deparaffinized with xylene at room temperature for 3 times (10 min each) and then rehydrated with ethanol gradient treatment, including two rinses in absolute ethanol, a rinse in 90%, 80%, and 70% ethanol, respectively (7 min each), and finally three rinses in distilled water (3 min each).…”
Section: Immunocytochemistry Analysismentioning
confidence: 99%
See 1 more Smart Citation